USE AND ANALYSIS OF THE COLLABORATIVE WALL IN THE TEACHING-LEARNING PROCESS ON HISTORY CONSIDERING DATA SCIENCE - Salas-Rueda, Ricardo-Adán; De-La-Cruz-Martínez, Gustavo; Alvarado-Zamorano, Clara; Prieto-Larios, Estefanía (Revista Conhecimento Online: Diversidade e Inclusão Social, 2021)
ABSTRACT This mixed research analyzes the use of the collaborative wall in the teaching-learning process on History considering data science and machine learning (linear regression). The sample is made up of 74 students from the National Preparatory School No. 7 “Ezequiel A. Chávez” who took the History course during the 2019 school year. The collaborative wall is a web application that facilitates the participation of students during the face-to-face sessions through the dissemination and organization of information on the Internet. During the face-to-face sessions, the students used mobile devices to share images and text through this web application. The results of machine learning indicate the dissemination and organization of information on the collaborative wall positively influence the participation of the students in the classroom, motivation and learning process on the characteristics of society during the sixteenth to eighteenth centuries. Data science identifies 6 predictive models on the use of the collaborative wall through the decision tree technique. Finally, the collaborative wall facilitates the construction of new educational spaces where students have the main role during the learning process on History. Keywords: Collaborative wall. Educational technology. Learning. Data science, Machine learning. RESUMO Esta pesquisa mista analisa o uso da parede colaborativa no processo de ensino-aprendizagem em História considerando a ciência de dados e o aprendizado de máquina (regressão linear). A amostra é composta por 74 alunos da Escola Preparatória Nacional nº 7 “Ezequiel A. Chávez” que fizeram o curso de História durante o ano letivo de 2019. O mural colaborativo é uma aplicação web que facilita a participação dos alunos durante as sessões presenciais através da divulgação e organização da informação na Internet. Durante as sessões presenciais, os alunos usaram dispositivos móveis para compartilhar imagens e texto por meio deste aplicativo da web. Os resultados do aprendizado de máquina indicam que a disseminação e organização das informações na parede colaborativa influenciam positivamente a participação dos alunos em sala de aula, a motivação e o processo de aprendizagem nas características da sociedade durante os séculos XVI a XVIII. A ciência de dados identifica 6 modelos preditivos sobre o uso da parede colaborativa por meio da técnica de árvore de decisão. Por fim, a parede colaborativa facilita a construção de novos espaços educacionais onde os alunos têm o papel principal durante o processo de aprendizagem da História. Palavras-chave: Parede colaborativa. Tecnologia Educacional. Aprendendo. Ciência de dados, aprendizado de máquina.